Influence of the actively migrated diagenetic elements on the hydrocarbon generation potential in tuffaceous shale. (15th November 2019) - Li, Yaohua; Yang, Wei; Wang, Qianyou; Song, Yan; Jiang, Zhenxue; Guo, Lishuang; Zhang, Yunpeng; Wang, Jianbo
Highlights: Rock pyrolysis parameter of (S1  + S2 )/TOC is used to indicate the organic reactions. Th and U clarify the contribution of active tuff component to hydrocarbon potential. Three diagenetic mineral trajectories are revealed by Gaussian elimination algorithm. Abstract: Source rock of tight oil is always associated with the tuff layers, i.e., the tuffaceous shale composed of the water-laid tuff and the detrital components. Most previous researchers focused on the influence of the water-laid tuff on the original organic matter (OM) productivity but ignored the organic-inorganic interactions in diagenesis. In this work, the element migration principles in tuffaceous shale was investigated to clarify their influence on the hydrocarbon generation using geochemical methods. Samples are collected from a complete interval of the Upper Triassic Yanchang Formation (Fm.) in Ordos Basin. 17 layers of tuffaceous shale and the adjacent black samples were tested for the mineral element contents, and the Rock-Eval hydrocarbon potential index (PI). Three diagenetic mineral trajectories related to the OM generation and evolution were proposed, i.e., the Fe-S cycle, the devitrification, and the apatite nodule formation, which drew the conclusions as follow: (1) A higher Fe/S value and a higher sulfate mineral content in the reducing environment benefit the hydrocarbon generation; (2) PI of the active tuff in the tuffaceous shale decreases with the zeolitization in the weak acidic or the freshwater environment, and increases with the potash feldspathization in the strong alkaline environment; (3) The alternate growth of apatite and hyalophane nodule could be viewed as an indicator of the organic-inorganic interactions, and the higher Ba/P values would benefit the OM generation.